Wind Power Plant Application With Permanent Magnet Synchronous Generator - Celikdemir, Soner; Ozdemir, Mehmet (Ieee, 2019)
Today, energy resources are rapidly decreasing. However, energy costs and environmental damage are increasing. In addition to the current situation, it is important to use new and renewable energy sources in energy production in order to meet the increasing energy needs. In this study, taking into consideration these situations, the design and experimental studies of the wind plant, which is one of the renewable energy sources, are examined. In addition, wind power, air duct and other circuit elements were designed by using low power permanent magnet synchronous generator (PMSG) and the characteristics of the wind turbine at different wind speeds were investigated. While all these are done, the primary objective is to examine the study in terms of applicability and to contribute to the dissemination of these systems.
4th International Conference on Power Electronics and their Applications (ICPEA) -- SEP 25-27, 2019 -- Elazig, TURKEY
Keywords: Wind Energy; Permanent Magnet Synchronous Generator (PMSG); Wind Power Simulation